The state of information literacy and user education programmes in public libraries in Tanzania: a case of National Central Library (NCL) and Kibaha Public Library - Lyakurwa, Balbina; Luambano, Ireneus (University of Dar es Salaam Library Journal, 2020)
The main purpose of this study was to examine the state of Information Literacy (IL) and user education programmes in public libraries in Tanzania. Specifically, the study aimed at examining methods used to deliver IL and user education skills in public libraries, assessing librarians ' competence in the delivery of IL and user education trainings, and identifying challenges facing IL and user education programmes in public libraries. The study was conducted in Dar es Salaam and Coast region; involving the National Central Library (NCL) and Kibaha Public Library respectively. The study used questionnaire, face to face interviews conducted with librarians, and observation methods to collect data. Quantitative data were analysed by using Statistical Product and Service Solutions (SPSS) while qualitative data were content analysed. The findings of this study have revealed that the major method of delivering information literacy and user education skills to library users was library tour. Due to lack of computers including internet connectivity, user training provided at Kibaha public library was confined to the delivery of traditional user education training. The findings have also revealed that although trainers possessed IL and user education knowledge, they lacked modern IL knowledge. The study also reveals that the major challenges facing IL and user education programmes in the public libraries include inadequate and outdated IL knowledge among trainers, inadequate teaching and learning facilities, inadequate management support, as well as limited awareness among library users on the importance of IL and user education training. Based on its findings, this study concludes that information literacy and user education trainings provision in public libraries is inadequate and therefore recommends computerising the public libraries, increasing financial support for IL and user education, as well as equipping trainers and librarians with updated knowledge on IL and user education.